2022
DOI: 10.3390/universe8060305
|View full text |Cite
|
Sign up to set email alerts
|

The Higgs Mechanism and Cosmological Constant Today

Abstract: The Higgs mechanism, as responsible for the first inflation, powers the initial accelerated expansion and further preheating via the symmetry breaking from its false vacuum state corresponding to the Sitter vacuum of the GUT scale with Λ=8πGρΛ, whose decay provides necessary energetic support. Here we address the question of the possibility of symmetry restoration of the Higgs field at the presently observed vacuum scale which would make it responsible for the today value of the cosmological constant λ=8πGρλ. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…The same is true for Λ(t) (see Figs 5,6). Taking into account relations connecting E(t) and Λ(t) and using ( 22), (23) and ( 27) one can conclude that there should be,…”
Section: Metastable States: Cosmological Applicationsmentioning
confidence: 61%
See 1 more Smart Citation
“…The same is true for Λ(t) (see Figs 5,6). Taking into account relations connecting E(t) and Λ(t) and using ( 22), (23) and ( 27) one can conclude that there should be,…”
Section: Metastable States: Cosmological Applicationsmentioning
confidence: 61%
“…In other words they showed that quantum decay processes can play an important role in the early Universe and their result means that all early universes, in which the the state describing their lowest energy was the quantum metastable vacuum state should decay and die sooner or later. Such a possibility of a tragic fate of the Universe has been discussed in many cosmological models (see e. g. [4,5,6,8,7,10,11,12,13,14,15,16,17] and also [18,19,20,21,22,23] and others). Some authors focus on the search for models in which the lifetime, τ F V 0 , of the false vacuum is much greater than the age of our Universe.…”
Section: Introductionmentioning
confidence: 99%
“…(A detailed discussion of this case is given in [53,[71][72][73]). At times t ∈ (T 1 , T 2 ) the energy E(t) is oscillatory modulated and decreases from the value E(t) = E 0 to the late time asymptotic value E lt (t) (see (27)). An analogous behavior takes place for Λ(t) at this time interval.…”
Section: Metastable States: Cosmological Applicationsmentioning
confidence: 99%
“…Such a possibility of a tragic fate of the Universe has been discussed in many cosmological models (see e.g. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] and also [22][23][24][25][26][27] and others). Some authors analyzing a fate of the Universe born in a metastable false vacuum state focus on the search for models in which the lifetime, τ F 0 , of the false vacuum is much longer than the age of our Universe.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of work has also been done to clear up some General Relativity challenges. An explanation for the problem of dark energy [10] and dark matter [11] is still being sought, and efforts are still b eing made to explain the origin of the cosmological constant [12], [13], [14].…”
Section: Introductionmentioning
confidence: 99%